COMPARATIVE STUDY BETWEEN DIGITAL AND CONVENTIONAL FINGERPRINTING USING ADDITION SILICONE - Bogdan Mihai Gălbinaşu; Andrei Iulian Păcuraru; Ion Pătraşcu (Amaltea Medical Publishing House, 2018)
The accurancy of digital models and digital impressions influence the clinical restorations. The aim of this study is to compare digital impression and the analog one, using time as the variable. Materials used for the classic stage were: acrylic cast resin, impression tray, impression material (EliteHD), extruded gypsum (Elite), vacuum mixer, and vibrating table. For digital impression there were used: acrylic cast resin, gypsum cast, scanning system Identica Blue, analysis software for virtual casts. The applied method consisted on using a cast of upper jaw, made of acrylic resin, on which were prepared type II cavities. After scanning this cast, it was obtained a virtual cast which was considered a refference as time x. Using the acrylic cast resin, there were taken impressions with addition silicon on tray, one stage, four different times. After that it was made the gypsum casts which will be scanned and turned into virtual as a STL file. The four STL files, after the four gypsum casts, and the refference cast at time x, were compared on sagitall and transverse planes, by making measurements on the preparation sites. Dimensions obtained after digital measurements vary during the selected period of time on both planes in order of tens of microns. Classic impression with addition silicon might be used as another way to have an impression than the digital one, regarding the dimensional stability and precission in detail reproduction.